Investigation of a Candida auris outbreak in a skilled nursing facility - Virginia, United States, October 2020-June 2021 (2023)
ABSTRACT: Candida auris, an emerging multi-drug resistant organism, is an urgent public health threat. We report on a C. auris outbreak investigation at a Virginia ventilator skilled nursing facility. During October 2020-June 2021, we identified 28 cases among residents in the ventilator unit. Genomic evidence suggested ≥2 distinct C. auris introductions to the facility. We identified multiple infection and prevention control challenges, highlighting the importance of strengthening multi-drug resistant organism prevention efforts at ventilator skilled nursing facilities.